The Influence Of Leadership Style And Work Spiriton The Productivity Of Section Employees Production At Pt Tirta Fresindo Jaya(Mayora Group) In Gowa District - Magfirahtun Tristiawati Rusli; Zalkha Soraya; Irwan Abdullah (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to describe and examine the influence of Leadership Style and Work Spirit on the Productivity of Production Employees at PT Tirta Fresindo Jaya (Mayora Group) in Gowa Regency, with a sample of 65 respondents. It was found that the significant value of leadership style (X1) on productivity (Y) is 0.014 < 0.05, and the calculated value is 2.517 > table value 0.2075. Meanwhile, the influence of work spirit (X2) on productivity (Y) is 0.003 < 0.05, and the calculated value is 3.069 > 0.2075. This type of research is quantitative, obtaining data from questionnaires distributed to respondents. In this study, data collection sources include primary and secondary data. The research instrument uses the Likert scale method. This study uses the scale method through the Statistical Package for the Social Sciences (SPSS) version 27 application. The author concludes that leadership style and work spirit have a positive and significant influence on the productivity of production employees at PT Tirta Fresindo Jaya (Mayora Group) in Gowa Regency.